Ökologische Bewertung von Lichtsystemen im Hinblick auf Anforderungen der EuP-Richtlinie. - Kroban, Malgorzata (My University, 2008)
Gegenstand der Arbeit ist eine vergleichende Ökobilanz in der Produktgruppe "Beleuchtung". Im Rahmen dieser Untersuchung ist eine Modellierung des gesamten Produkt-Lebenszyklus aller Komponenten zweier unterschiedlicher Lichtsysteme, bestehend aus Leuchtstofflampe, Vorschaltgerät und Leuchte, vorgenommen worden. Um die ökologischen Auswirkungen aller Komponenten des Lichtsystems zu ermitteln, wurden alle Umweltauswirkungen während der gesamten Herstellungs- und Nutzungsphase erfasst und bewertet. Durch die vorgeschlagene Bewertungsmethode kann der Kunde auf einfache Weise unterscheiden, welche Produkte eine geringere Energieeffizienz und daraus resultierend schlechte Systemausbeute besitzen sowie welche die "best in class" sind. Darüber hinaus ist der Weg für die Produktumweltdeklaration geschaffen, die ein unersetzliches Werkzeug bei Maßnahmen zur Steigerung der Energieeffizienz bildet.

Subject of the work is a comparative life cycle assessment in the product group "lighting". The study models the total product life cycle of all components of two different lighting systems each composed of a fluorescent lamp, an electronic control gear and a luminaire. To assess the ecological impacts of all components of the lighting systems, their respective environmental impact during the production and use phase was compiled and evaluated. The description of the environmental impacts over the lifetime is realised with the support of classes of environmental impact . The analysis shows that within the product life cycle, the impact of the use phase is dominant with more than 99% of the total ecological impact. This leads to the conclusion that future improvements in the lighting industry must focus on the product design relevant for the use phase. The most important criterion is energy efficiency (efficacy). In a further step, a range of criteria relevant for the evaluation of lighting systems was developed based on the results of the assessment. As the study shows that the use phase has the highest environmental impact, the parameters are chosen to reflect this phase. The assessment method complies with the requirements of the directive on the Eco - Design Requirements for Energy using Products . The presented assessment method is a tool for preparing environmental product information and facilitates decisions regarding the selection of the best system components. The assessment method thus offers a clear and simple method to select energy efficient components for lighting systems. The modular assessment, which is the basis of this paper, favourably supports a previously disregarded issue: the customer s decision process when buying energy efficient products. Because of the modular structure the customer can create a virtual lighting system and benchmark it in a simple way with comparable products. An additional goal of the study was the creation of a framework for the use for eco profiles according to the EuP-directive. Because the main focus of the directive is the reduction of energy consumption, such a tool should clearly show environmental impacts and point out reduction potentials. Using the shown assessment method the customer can easily discern products with a low energy efficiency and a resulting bad system output from those which are "best in class". Furthermore, the method allows the preparation of environmental product declarations, which are an irreplaceable tool for measures increasing energy efficiency.
Ecological valuation of lighting systems with regard to requirements of the EuP directive.
Keywords: Energie; Energieeinsparung; Leuchtstofflampe; Beleuchtung; Leuchte; Entsorgung; Nutzung; Bewertungsmethode; Energieeffizienz; Ökologische Bewertung; Umweltbilanz; Produktbilanz; Lebenszyklus; EU-Richtlinie; Ökobilanz